Analysis of the etiopathogenic factors of lumbar disc disease and kinetic approach to stabilize the somato-functional status - Mihai Constantinescu (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement)
In this paper we will address a problem that is as topical as possible and at the same time quite well studied in research in this area. Due to a very fast-running lifestyle with activities that overload the human body, it is no longer able to cope with the demands, and as a consequence of physical stress and the inability to recover in time, the disease easily takes hold on a vulnerable ground. Lumbar disc disease is a fairly common condition, but the way it is treated is flawed. People who have been diagnosed with this condition have not received conservative treatment, but rather have stayed in pain and disability until surgery was needed. In the direction of this problem we will present some aspects of the installation of pathological conflict in the spine but at the same time we will elaborate a therapeutic pathway leading to the prevention of complications and stabilization of spine function.